IS231A from Bacillus thuringiensis is functional in Escherichia coli: transposition and insertion specificity. - Hallet, B (1991)
A kanamycin resistance gene was introduced within the insertion sequence IS231A from Bacillus thuringiensis, and transposition of the element was demonstrated in Escherichia coli. DNA sequencing at the target sites showed that IS231A transposition results in direct repeats of variable lengths (10, 11, and 12 bp). These target sequences resemble the terminal inverted repeats of the transposon Tn4430, which are the preferred natural insertion sites of IS231 in B. thuringiensis.